The effect of audit opinion and auditor reputation on audit report lag in the banking industry listed on the Indonesia Stock Exchange - Anan, Malesa; Abdul Halim, Hazianti (International Journal of Accounting, Finance and Business, 2026)
This study aims to analyze the effect of audit opinion and auditor reputation on audit report lag, in banking industry listed on the Indonesia Stock Exchange for the period 2017– 2024. This study was developed based on signaling theory, institutional theory, agency theory, and audit risk model to explain the direct relationships between the research variables. The research method used a quantitative approach with secondary data obtained from audited financial statements. The research sample consisted of 336 company-period observations. Data analysis was performed using the Python programming language to support data processing accuracy and efficiency. Hypothesis testing was conducted through multiple linear regression with the application of robust standard errors to overcome classical assumption violations. The results show that audit opinion has a positive and significant effect on audit report lag, meaning that companies receiving modified opinions tend to experience longer audit delays. Auditor reputation, proxied by Big Four affiliation, has a negative and significant effect on audit report lag, indicating that reputable auditors are able to complete audits more timely. This study provides theoretical and practical contributions to understanding the determinants of audit report lag in Indonesia.